Modeling and control of a rotary inverted pendulum using various methods, comparative assessment and result analysis - Akhtaruzzaman , Md.; Shafie, Amir Akramin (2010)
Inverted pendulum control is one of the fundamental but interesting problems in the field of control theory. This paper describes the steps to design various controllers for a rotary motion inverted pendulum which is operated by a rotary servo plant, SRV 02 Series. In this paper some classical and modern control techniques are analyzed to design the control systems. Firstly, the most popular Single Input Single Output (SISO) system, is applied including 2DOF Proportional-Integral-Derivative (PID) compensator design. Here the common Root Locus Method is described step by step to design the two compensators of PID controller. Designing the control system using 2DOF PID is quiet challenging task for the rotary inverted pendulum because of its highly nonlinear and open-loop unstable characteristics. Secondly, the paper describes the two Modern Control techniques that include Full State Feedback (FSF) and Linear Quadratic Regulator (LQR). Here FSF and LQR control systems are tested both for the Upright and Swing-Up mode of the Pendulum. Finally, experimental and MATLAB based simulation results are described and compared based on the three control systems which are designed to control the Rotary Inverted Pendulum. © 2010 IEEE.